UJI BAKTERIOLOGIS SERAI GILING (Andropogon nardus L.) YANG DIJUAL DI PASAR RAYA KOTA PADANG - Ika Putri, Roza; Periadnadi, Periadnadi; Indriati, Gustina (STKIP PGRI Sumbar, 2014)
ABSTRACTOne of food matherial which can cause problem in food safety is grinded spice, grindedspice used by restaurant and house wife who do not have much time to grind the fresh spice, morever it is needed in great quantity, one of them is grindedlemon gress. The research is aimed to test bacteriolgically of the grindedlemon grass (Andropogon nardus L.) which sold at traditional market of Padang City. The research was doing on July 2013 in Microbiology Laboratoy of Depatment of Biology, the Faculty of Mathematcs and Natural Sciences Andalas University. This research done by using descriptive method, the samples were purchased randomly purchased in the market and wereexamined for the presence of E.coli and other Coliform bacteria. The bacteriology test consisted of Presumtive test, Comfirmed test, and Completed test by determining of Most Probable Number (MPN)of 5:1:1 dilution serial.the result showed that the samples contained the hishest total bacteriaof 135x 107 /g found by samples D and the lowest total bacteria of 63x 107/gfound by the samples B.Fife of seven7 samples were positve contained E.coli, while the otheswere positive colifom. Due to the result of the study, the samples of grinded lemon gress sold in the traditional market of padang are no yet eligible to be consumed.